Elektromobilität in der deutschen Landwirtschaft: Eine qualitative Analyse zur Nutzerakzeptanz; E-Mobility in German Agriculture - A Qualitative Analysis of User Acceptance - Friedrich Rub̈cke von Veltheim; Ansgar A. Rube; Heinke Heise (German Journal of Agricultural Economics (GJAE), 2021)
– The development of battery-powered tractor concepts reveals that the topic of electric mobility in agriculture is becoming increasingly relevant. However, it is not yet clear whether these concepts can be established on a broad scale or remain as niches. It is a fact that the future acceptance of e-mobility among farmers will play a key role in this context. But compared to the automotive sector, little is known about the ex-ante user acceptance of electrically powered agricultural machinery. Therefore, this explorative study examines the influencing factors of the ex-ante user acceptance of electrically driven agricultural machinery in a qualitative way in order to contribute to further research on user acceptance. With the help of qualitative expert interviews, 15 farm managers of differently organized agricultural farms were interviewed on this topic. It turns out, that the majority of the interviewees are critical in terms of the distribution and use of e‑mobility in agriculture. On the other hand, it has been shown that the ex-ante user acceptance of electrically powered agricultural machines is not only influenced by various factors, but that they are also linked to each other and thus have an indirect effect on the ex-ante user acceptance of the respondents.
Keywords: 330; deutsche Landwirtschaft; Elektromobilität; Landma-schinen; Nutzerakzeptanz; qualitative Experteninterviews; Technologieadoption